Pengaruh Persepsi Pemanfaatan Media Pembelajaran E-commerce Terhadap Minat Wirausaha Siswa SMK Gajah Mada 3 Palembang - Sari, Kadek; Erma Yulaini; Januardi (Bedelau: Journal of Education and Learning, 2024)
This research aims to investigate the effect of using e-commerce learning media on students' entrepreneurial interest at SMK Gajah Mada 3 Palembang. Based on the background and limitations of the problem in this research, it is to find out whether there is an influence of perceptions regarding the use of e-commerce learning media on the entrepreneurial interest of students at SMK Gajah Mada 3 Palembang. The research methodology used in this data collection technique is documentation and questionnaires. Based on the research conducted, there are results from research that has been carried out. The results can be seen. So it can be concluded that the constant value is 100.214, meaning that if the perception of using e-commerce learning media (X) is 0, then the student's entrepreneurial interest will be negative (Y), namely 0.176, meaning that if the perception If the use of e-commerce learning media increases, interest in entrepreneurship will increase by 0.176, the coefficient is positive, so the relationship between the two variables, perception of use of e-commerce learning media (X) and Entrepreneurial Interest (Y), the higher the level of perceived value of use, the more interest. students to become entrepreneurs. Thus, it means that there is an influence of e-commerce learning media on the entrepreneurial interest of students at SMK Gajah Mada 3 Palembang. Efficacy using the Kolmogorov – Smirnov test, Levene's Homogeneity Test, and the simple Linear test were used to test questionnaire data on students. Keywords: E-commerce Learning Media, Student Entrepreneurial Interest